ANALISIS PERUBAHAN TARIF RETRIBUSI PARKIR DI TEPI JALAN UMUM KABUPATEN BATANG - Choliq Sabana; Danang Satrio (Fakultas Ekonomi Universitas Pekalongan, 2018)
The achievement of the parking retribution target from 2012 to 2016 shows a satisfactory figure, this can be seen from the target target ratio and the realization of all above 100%. However, if it is studied more deeply in common size, by making the parking retribution in the year concerned as a common basis, then there is a tendency to decrease in percentage. Thus the Batang Regency Government feels that it is necessary to conduct a more in-depth study of the potential available with the realization of parking fees and need to be more prudent in making decisions related to the policy of increasing PAD (Locally-generated revenue) through policies to increase regional fees including parking fees. Keywords: Parking Retribution, Locally Generated Revenue, Batang Regency Government